Faktor-Faktor yang Berhubungan dengan Pemanfaatan Buku Kesehatan Ibu dan Anak (KIA) Oleh Ibu Hamil - Maratun Hasanah; Desy Susanti (Jurnal Akademika Baiturrahim Jambi, 2023)
The coverage of MCH handbooks in Jambi Province is only around 72.34% where the target coverage is 100%. Seen from the withdrawal of the distribution of the MCH handbook received by the Puskesmas in Jambi Province, it reached 90%, however, the utilization of the MCH handbook was still low. The aim of the study to determine the relationship between knowledge, attitude and education of pregnant women in using the MCH handbook. The research method uses analytic observational with cross sectional. The study population was pregnan women who checked their pregnancies in the Working Area of the Bingin Teluk Health Center during the study. The sampling technique used purposive sampling based on the inclusion criteria of 70 respondents. Data analysis test using Fisher’s Exact. The result showed thet there was no relationship between knowledge and the use of the MCH handbook with a p-value of 0.062, OR of 0.078 (0.001-0.946). There is no relationship between attitude and utilization of the MCH handbook with a p-value of 1.000, OR of 0.841 (0.758-0.932). There is a relationship between education and the utilization of the MCH handbooks with a p-value of 0.044, with an OR of 0.198 (0.045-0.880).The conclusion of this study is that tehre is no relationship between the knowledge and attitude of pregnant women and the use of the MCH handbooks and there is a relationship between the education of pregnant women and the users of the MCH handbook in the Working Area of the Bingin Teluk Health Center.